SGK1 in Human Cancer: Emerging Roles and Mechanisms - Sang, Yiwen; Kong, Piaoping; Zhang, Shizhen; Zhang, Lingyu; Cao, Ying; Duan, Xiuzhi; Sun, Tao; Tao, Zhihua; Liu, Weiwei (Frontiers in Oncology, 2021)
Serum and glucocorticoid-induced protein kinase 1 (SGK1) is a member of the ‘AGC’ subfamily of protein kinases, which shares structural and functional similarities with the AKT family of kinases and displays serine/threonine kinase activity. Aberrant expression of SGK1 has profound cellular consequences and is closely correlated with human cancer. SGK1 is considered a canonical factor affecting the expression and signal transduction of multiple genes involved in the genesis and development of many human cancers. Abnormal expression of SGK1 has been found in tissue and may hopefully become a useful indicator of cancer progression. In addition, SGK1 acts as a prognostic factor for cancer patient survival. This review systematically summarizes and discusses the role of SGK1 as a diagnostic and prognostic biomarker of diverse cancer types; focuses on its essential roles and functions in tumorigenesis, cancer cell proliferation, apoptosis, invasion, metastasis, autophagy, metabolism, and therapy resistance and in the tumor microenvironment; and finally summarizes the current understanding of the regulatory mechanisms of SGK1 at the molecular level. Taken together, this evidence highlights the crucial role of SGK1 in tumorigenesis and cancer progression, revealing why it has emerged as a potential target for cancer therapy.